Pengabdian Masyarakat Pembacaan Naskah Babad dan Perawatan Lontar di Dadia Pasek Gelgel Aan Padangaji Kebon, Pering Sari, Karangasem - Widiantana, I Kadek (Sevanam: Jurnal Pengabdian Masyarakat, 2023)
Bali inherited thousands of lontar manuscripts which are treasures of noble knowledge inherited from Balinese ancestors. But in the midst of this rich heritage, the inheritance of the ability to study the contents of lontar is seen as a decline. The ability of Balinese human resources to write, read, let alone understand or study the contents of lontar is very limited, so that much of this inherited knowledge is neglected because it is beyond the reach of the people who inherit it. One of them is the legacy of knowledge about the journey of the ancestors in Dadia Pasek Gelgel Aan Padangaji, Pering Sari, Karangasem. The lack of public knowledge about the contents of the lontar and the procedures for caring for them makes it important to carry out community service activities in the form of reading lontar manuscripts, including conveying the procedures for caring for an ancient manuscript. The methodology used in this dedication is through coaching, reading lontar, and indirectly also using a philological approach. From the dedication carried out, it was found that the manuscript in the form of the babad was not intact, because there were parts that were missing and damaged. Therefore, apart from reading the manuscript, digitization and transliteration of the manuscript were also carried out.